EXPRESSIVE SPEECH ACTS IN THE FILM “172 DAYS” BY NADZIRA SHAFA: TINDAK TUTUR EKSPRESIF DALAM FILM “172 DAYS” KARYA NADZIRA SHAFA - Syaharani Gustiawati; Imam Safi’i (Jurnal Kata, 2024)
This study aims to analyze the form and function of expressive Speech acts in the film “172 Days” by Nadzira Shafa. The method used in the research is a qualitative descriptive method with the data source of  “172 Days” film and data in the form of expressive speech acts between characters in the film. There are two data collection techniques, namely : 1) listening technique and 2) note taking technique. The results of the research show that the expressive speech acts contained in the film “172 Days” are very diverse, namely in the form of expressions of expressing gratitude, expressing praise, apologizing, blaming, expressing condolences, and saying congratulations. The function of expressive speech acts is the function of expressing thanks, expressing praise, apologizing, blaming, expressing condolences, and congratulating.